TOURISM AND TECHNOLOGY: REVISITING THE EXPERIENCES OF WOMEN TRAVELLING ALONE - Fiona Jordan (Proceeding International Conference on Information Technology and Business, 2016)
This paper revisits some of the key concepts I used in my original research into solo female tourists in the 1990s to explore how technology impacts upon, and influences, the experiences of women travelling alone. The paper reviews the market for solo female travel since the 1990s and the ways in which technology is helping to shape its growth. It also considers the influence of technology on the experiences of travel with particular regard to its impact on the performance of tourists, and surveillance and security in tourism.